2020
DOI: 10.1016/j.optmat.2019.109630
|View full text |Cite
|
Sign up to set email alerts
|

Optical modes of multilayered photonic structure containing nematic layer with abnormal electroconvective rolls

Abstract: Optical modes of a multilayered photonic structure with the twisted nematic liquid crystal as a defect layer have been investigated. The electroconvective flow in the nematic makes a spatially periodic structure in the form of abnormal rolls. Non-adiabatic propagation of polarized light in the defect layer causes unique features of the optical modes corresponding to the ordinary o-waves. The decay of these modes has been demonstrated with increasing voltage due to the effect of cross-polarization diffraction l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[27][28][29][30][31][32][33][34] It has been repeatedly demonstrated that EHD-induced periodic DGs can also be promising for beam steering applications 28 in various optoelectronic devices, such as tunable spectral filters, polarizing sensors, etc. 29 Recently, a fascinating example of light-driven EHD instabilities was demonstrated by G. Zhou et al 30 The LC mixture with a high negative dielectric anisotropy (De = À8.3) was doped with the spiropyran photochromic substance. Application of an electric field in the absence of UV light induces reorientation of the homeotropically aligned liquid crystal perpendicular to the electrical field direction driven by its negative dielectric anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34] It has been repeatedly demonstrated that EHD-induced periodic DGs can also be promising for beam steering applications 28 in various optoelectronic devices, such as tunable spectral filters, polarizing sensors, etc. 29 Recently, a fascinating example of light-driven EHD instabilities was demonstrated by G. Zhou et al 30 The LC mixture with a high negative dielectric anisotropy (De = À8.3) was doped with the spiropyran photochromic substance. Application of an electric field in the absence of UV light induces reorientation of the homeotropically aligned liquid crystal perpendicular to the electrical field direction driven by its negative dielectric anisotropy.…”
Section: Introductionmentioning
confidence: 99%